A Panel Study on the Impact of Labor Market Freedom on the Female Labor Force Participation Rate Across the World - Nazmul Islam (European Economic Letters (EEL), 2025)
This paper explores whether a greater degree of labor market freedom leads to an increase in the female labor force participation rate (FLFPR) by examining the country-level panel dataset across the world. In the study, we employ the labor market regulation (LMR) index to present labor market freedom. We find a positive association between LMR index and FLFPR using the countrywide panel data without fixed effects. This result implies that, other things remaining the same, a 1% increase in the LMR index would lead to a 0.116% increase in the FLFPR in the world. However, there exists a negative association between the LMR index and FLFPR for the fixed effects models. Economic policy reforms can substantially enhance the FLFPR in the job markets in countries with heavily regulated labor markets.